Hackberry Nipplegall Maker (Psyllids) - Bauernfeind, Robert J. (My University, 2007)
Publication describes hackberry nipplegall maker insects also known as psyllids, for homeowners with hackberry trees.
MF957_2007_05
Keywords: MF957; Insects; MF